Problems and Loopholes in the Offense of Insulting or Disrespecting a Corpse under the Thai Criminal Code - Chongchitcharoenporn, Wittawin (Journal of Thai Ombudsman, 2026)
This academic article examines the offense of insulting or disrespecting a corpse under Section 366/4 of the Thai Penal Code, which aims to protect human dignity even after a person has ceased to exist as a legal person. It also seeks to safeguard the rights of family members, as well as honor and reputation, which are rights guaranteed by the Constitution. The author therefore aims to study the differences between the offense of insult, other defamation-related offenses under the Penal Code, and the offense of insulting a corpse in foreign jurisdictions, in order to compare and further develop this offense to ensure the most comprehensive protection possible. The study also proposes improvements to align the offense of insulting a corpse with other offenses of insult and defamation under the Penal Code. This research employs a qualitative methodology based on documentary sources, including academic articles, journals, books, and legal materials from both Thailand and other countries. The findings reveal that the offense of insulting a corpse constitutes a public offense rather than a compoundable offense, which distinguishes it from defamation under Section 326 and defamation of the deceased under Section 327. It is also not classified as a petty offense, unlike the offense of face-to-face insult under Section 393. Furthermore, the provision does not extend to acts of insult directed at representations of the deceased. The author observes that the structure of penalties, elements of the offense, and applicable general principles make criminal proceedings in such cases more stringent and more difficult to settle compared to offenses of insult or defamation against living persons. Additionally, the current scope of the offense does not cover other representations of the deceased. Therefore, it is suggested that the law should be amended to include acts of insult toward such representations in order to provide more comprehensive legal protection.